Veterans Action League 2.0: Creating a Veteran-Centered Chronic Pain Research Agenda - Cheryl A. Krause-Parello; Linda Flynn; Beth A. Pratt; Rosa Clarke; Luana Colloca; Jane Garvin; David Hibler; Karen L. Saban; Frances Weaver (The University of Alabama, 2023)
Chronic pain is the leading cause of disability among United States veterans. Affecting up to 70% of veterans, chronic pain touches all aspects of life, not just physical functioning. Despite the fact that the nation is experiencing a crisis with substance use disorder, the most common treatment for pain among veterans is opioids. The purpose of this community engagement project was to develop a national veteran-centered chronic pain research agenda. In total, 129 veterans and stakeholders engaged in Think Tank Meetings across five states: Florida, Georgia, Illinois, North Carolina, and Virginia. Veterans revealed they wanted better access to care, better care coordination, and more options for managing chronic pain. Veterans' recommendations for chronic pain management and veteran-generated priorities for chronic pain research are presented. The outcomes of this community engagement project can be used by researchers, clinicians, health care providers, health care system managers, and policy-makers to engage in activities that are veteran-centered and veteran-driven.